2011
DOI: 10.1111/j.1365-3180.2011.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Control measures for a recent invasion of Hieracium pilosella in Southern Patagonian rangelands

Abstract: Plant invasions have important ecological impacts on biodiversity, the functioning of ecosystems and economic sustainability. In this study, we evaluated the effects of four control measures (pasture sown + fertiliser, fertiliser and selective ⁄ non-selective herbicide applications) in two different grazing conditions (grazed and ungrazed) during a recent invasion of the exotic herb Hieracium pilosella in northern grasslands of Tierra del Fuego Island in Southern Patagonia, Argentina. As response variables, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…In addition, these results contribute to the state of progress of the invasive species Hieracium pilosella in the Fueguian steppe and to the knowledge of the incorporation of this species in the diet of livestock, and possibly in that of native herbivores. [61][62][63]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these results contribute to the state of progress of the invasive species Hieracium pilosella in the Fueguian steppe and to the knowledge of the incorporation of this species in the diet of livestock, and possibly in that of native herbivores. [61][62][63]…”
Section: Resultsmentioning
confidence: 99%
“…Объясняется это быстрым разрастанием его из-за интенсивного вегетативного размножения с помощью надземных столонов. Именно по этой причине данный вид широко распространился по всему миру за пределами своего естественного ареала -в Северную и Южную Америку, Тасманию и Новую Зеландию, куда был интродуцирован как декоративное растение или занесен с семенами сельскохозяйственных культур (Webb et al, 1988;Rudman, Goninon, 2002;Gawrońska-Grzywacz et al, 2011;Cipriotti et al, 2012;USDA-NRCS, 2016). На этих континентах и островах H. pilosella рассматривается как агрессивный инвазивный вид, наносящий урон аборигенной флоре и сельскому хозяйству (Grundy, 1989;Wilson et al, 1997;Rudman, Goninon, 2002;USDA-NRCS, 2016).…”
Section: Hieracium Pilosella L (Pilosella Officinarumunclassified
“…Intake was observed, with low frequency, in all diets the presence of an invasive species, Hieracium pistosella, which is being studied for its degree of progress in Tierra del Fuego. 23,39,40 When comparing the diet composition to the main components analysis, according to components 1 and 2 (97% of total variability), it was observed that cows and sheep group by the HD intake frequency (Figure 3), whereas guanacos differ according to the sampling area. The guanaco diet in the EaSJ was different from the others because of the intake frequency of Gr and SG; whereas in EaBa the diet was different due to the presence of bush species; and in EaU because of the intake of MLB (Figure 3).…”
Section: Eaba Easjmentioning
confidence: 99%